Adjustment of models of seven probability distribution density to historic series of monthly relative humidity in Mossoró – RN - Assis, Janilson Pinheiro de; Sousa, Roberto Pequeno de; Silva, Roseano Medeiros da; Linhares, Paulo César Ferreira (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2013)
The objective was to check the fit of 12 time series of monthly relative humidity (%) from 1970 to 2007in Natal, RN, seven models of the probability density distribution Normal, Log-Normal, Beta, Gamma, Log-Pearson (Type III), Gumbel and Weibull, through the Kolmogorov-Smirnov test, chi-square, Cramer-Von Mises, Anderson Darling, Kuiper, a 5% probability and the logarithm of maximum likelihood. It was the superiority of the adjustment range of distributions, Gamma, Gumbel and Normal, compared with the other fox distributions. In general, the adjustment criteria agreed with the acceptance of the H0hypothesis. However, it should be noted that the Kolmogorov-Smirnov test shows a level of approval of a distribution under test very high, which creates some uncertainty to the test criteria, but in this study as the data is approximately symmetric it is recommended.